Kajian Teori dan Pandangan Alkitab Mengenai Kepemimpinan Transformasional - Adi Suhenra Sigiro; Fitri Lyli Septiani Sitompul; Andhika Sinaga; Pirianus Mom (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2025)
Transformational leadership is an approach that emphasizes inspiration, empowerment, and individual development in order to achieve organizational goals holistically. This study aims to examine the concept of transformational leadership theoretically, while reviewing its application in the context of general organizations and churches, and its relevance according to the biblical perspective. Using the literature study method, this study collected data from various scientific literature and theological sources to build a solid conceptual framework. The results of the study indicate that transformational leadership has significant benefits, such as increasing employee engagement, innovation, and performance. On the other hand, this approach also has limitations, especially in the context of organizations that are bureaucratic or still in the early stages of formation. From a biblical perspective, transformational leadership is in line with the examples of Deborah and Jesus Christ, who led through service, example, and personal transformation. Thus, transformational leadership is not only relevant to the development of modern organizations, but also has a strong spiritual basis in Christian teachings.